2009
DOI: 10.1086/594372
|View full text |Cite
|
Sign up to set email alerts
|

Oral Therapeutic Vaccination withStreptococcus sobrinusRecombinant Enolase Confers Protection against Dental Caries in Rats

Abstract: Dental caries is among the more prevalent chronic human infections for which an effective human vaccine has not yet been achieved. Enolase from Streptococcus sobrinus has been identified as an immunomodulatory protein. In the present study, we used S. sobrinus recombinant enolase (rEnolase) as a target antigen and assessed its therapeutic effect in a rat model of dental caries. Wistar rats that were fed a cariogenic solid diet on day 18 after birth were orally infected with S. sobrinus on day 19 after birth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…As we expected, we found that immunization with enolase confers protection against lethal SS2 infection in mice, prompting us to believe it could potentially be a candidate subunit vaccine against infection by the bacteria [18,19]. Very recently, a similar finding was reported regarding Streptococcus sobrinus, which indicated that oral therapeutic vaccination with recombinant enolase confers protection against dental caries in rats [30]. The findings that facilitated the design of a highly effective epitope vaccine prompted us to further address B cell epitopes and MHC II-restricted peptides for SS2 enolase (data not shown).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As we expected, we found that immunization with enolase confers protection against lethal SS2 infection in mice, prompting us to believe it could potentially be a candidate subunit vaccine against infection by the bacteria [18,19]. Very recently, a similar finding was reported regarding Streptococcus sobrinus, which indicated that oral therapeutic vaccination with recombinant enolase confers protection against dental caries in rats [30]. The findings that facilitated the design of a highly effective epitope vaccine prompted us to further address B cell epitopes and MHC II-restricted peptides for SS2 enolase (data not shown).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, these enzymes play critical roles in bacterial colonization, persistence, and invasion of host tissue, in addition to their innate glycolytic and metabolic enzyme activities [29]. Enolase, an enzyme responsible for the dehydration of 2-phosphoglycerate (2-PGE) to phosphoenolpyruvate (PEP), was recognized recently as an immunodominant antigen involved in the virulence of Streptococcus species [24,27,30,31].…”
mentioning
confidence: 99%
“…Thus, it can be concluded that cell surface enolase does contribute to bacterial virulence. Interestingly, in this context, it has been reported that the recombinant enolase from the oral bacterium Streptococcus sobrinus is an immunosuppressive protein (180) which can be used, if administered orally, to protect against dental caries in the rat (50). In contrast, with Paenibacillus larvae, the Grampositive causative agent of American foulbrood (AFB), which affects the larvae of the honeybee, Apis mellifera, the enolase is a secreted highly immunogenic protein which is thought to play a role in the virulence of this bacterium (9).…”
Section: Moonlighting Bacterial Glycolytic Enzymesmentioning
confidence: 99%
“…Whether these antibodies are protective or simply a response to colonization is difficult to elucidate, since interpretation of human studies is confounded by study variation and the numerous factors influencing caries development (reviewed in Smith and Mattos-Graner, 2008). Nonetheless, vaccine studies in animal models of dental caries demonstrate the potential for manipulating the immune response to generate specific antibodies, which may reduce colonization and subsequent caries in these animals (Culshaw et al, 2007;Dinis et al, 2009Dinis et al, , 2011. The mechanisms driving these immune responses are unknown, and although the potential exists for individuals to raise antibodies to Streptococcus mutans, to date, this has proved challenging to manipulate effectively.…”
Section: Introductionmentioning
confidence: 99%